TEMUAN HOMO FLORESIENSIS DI SITUS LIANG BUA - Jatmiko, nfn; Sutikno, Thomas (Balai Arkeologi Kalimantan Selatan, 2006)
Liang Bua, a limestone cave on the Manggarai hil(s in West Flores, has become well known and exposed internationally due to the discovery of a ofelatively complete skeleton including its lithics and endemic faunal remains. These findings were the result of excavation scarried out in 2003 and 2004. The human remain was identified as 'Homo floresiensis' and dated 38,000-18,000 BP. A group of scientists claims that 'Homo floresiensis' is one of the most spectacularr of this decade. The discovery opens up a new perspective for the study of human evolution. On the other hand, another group of experts perceives 'Homo floresiensis' of Liang Bua as 'Homo sapiens' similar to modern human today, which indicates physical defect suffering from microcephaly. Both suggestions have become a lengthy scientific dispute among scientists. Nonetheless, a simple question still lingers on: what and who is the 'Homo floresiensis'?